Nuevas contribuciones en monocotiledóneas mexicanas III (Orchidaceae, Poaceae) - López-Ferrari, Ana Rosa; Espejo Serna, Adolfo (Instituto de Ecología, A.C., 2000)
The following new combinations are provided: Anthaenantia villaregalis (McVaugh & R. Guzmán) Espejo & López-Ferrari, Panicum macrospermum (Gould) Espejo & López-Ferrari, Urochloa jaliscana (F. Santana) Espejo & López-Ferrari, Prosthechea pastoris (Lex.) Espejo & López-Ferrari and Isochilus bracteatus (Lex.) Salazar & Soto Arenas. The neotypes of Epidendrum pastoris Lex. and Dendrobium bracteatum Lex. are designated.